Peran UPT-BP2MI DIY Dalam Pemberdayaan Pekerja Migran Indonesia Purna Dan Implikasinya Terhadap Ketahanan Ekonomi Keluarga - Dwi Hartanto1 (Jurnal Ketahanan Nasional, 2022)
ABSTRACT            This study aimed to analyzed the role of UPT-BP2MI DIY in empowering PMI Purna and analyzed its implications for family economic resilience. This study used the theory of role, empowerment and the theory of family economic resilience. This research approach was a qualitative research with descriptive exploratory method with data collection techniques used were observation, interviews, documentation and literature. The informants in this study amounted to 13 people consist of employees of UPT-BP2MI DIY and PMI Purna. Data analysis used was data categorization, data reduction, data presentation, and drawing conclusions.The results of this study indicated that through the empowerment of PMI Purna organized by UPT-BP2MI DIY it had implications for increasing insight, skills, and abilities to created independence and economic resilience for PMI Purna families. In its implementation, there were still obstacles faced by UPT-BP2MI DIY and PMI Purna for implementing the results of empowerment. The empowerment activities carried out had implications for the economic resilience of PMI Purna's families, which could be seen through four aspects, namely: (1). Family residence, (2). Family income that had exceeded the Provincial Minimum Wage (UMP) of DIY Province of Rp. 1,765,000 rupiah, this was one of the strongest aspects of determining the implications of PMI Purna's family economic resilience, (3). Financing the education of children who did not drop out of school in the 12-year compulsory education, and (4). Family financial guarantees in the form of bank products, non banks and others.